One of us … and us … and us: Evidence that leaders' multiple identity prototypicality (LMIP) is related to their perceived effectiveness. Issue 2 (4th May 2018) - Steffens, Niklas K.; Peters, Kim; Haslam, S. Alexander; Platow, Michael J.
ABSTRACT: The social identity approach to leadership has focused on examining how leaders' (single) group prototypicality (i.e., the extent to which a leader is seen to embody what it means to be "one of us") affects various follower and organizational outcomes. The current registered report advances this approach by introducing the idea of leader multiple identity prototypicality (prototypicality of multiple group memberships that are shared between leaders and followers). Examination of a large sample of employees ( N = 611) supported the core hypothesis that leaders' multiple identity prototypicality is associated with followers' stronger personal identification with leaders, as well as greater leader endorsement and charisma. Furthermore, as anticipated, there was evidence of an indirect effect such that leader multiple identity prototypicality was positively associated with followers' identification with their leader and, through this, with leader endorsement and perceptions of the leader's charisma. The present findings have implications for the social identity approach to leadership, as well as research on intergroup leadership and leadership of diverse groups. The pre-registration can be found in the Open Science Framework Registries (https://osf.io/tf3qs ). All materials including survey questions, data, and analysis code are openly accessible on the Open Science Framework's project page:https://osf.io/ceapq/ .